Exploration of COVID‐19 related fears deterring from blood donation in India. (9th March 2021) - Sachdev, Suchet; Kishore, Kamal; Singh, Lakhvinder; Lamba, Divjot Singh; Hans, Rekha; Dhawan, Hari Krishan; Grover, Sandeep; Sharma, Ratti Ram
Abstract : Introduction: The coronavirus pandemic (COVID‐19) has impacted and pushed the healthcare settings to extremes across the globe. It was extremely challenging to sustain blood donation, and strategies could be formulated on knowing fears hindering blood donation. Methods: A cross‐sectional survey using Google Forms ® through WhatsApp and email after obtaining the ethical clearance. The survey questionnaire was validated for content using the Delphi technique, and pilot tested for finalization. Results: The survey was attempted by 1066 participants, and 749 participants who had not donated since pandemic were included in the study. A little more than half, 415 (55%) reported either one or more than one fear during the pandemic which hindered blood donation. They reported lack of confidence in the safety measures at the hospitals and fear of transmitting infection to family, in 415 (55%) of the participants each, respectively. The fear of COVID‐19 hospital infection risk and hospital entry was statistically significant across the age groups that are eligible for blood donation. Conclusions: The clear and dedicated confidence building measures to sustain blood donation using all communication modalities clearly emerge as the most important strategies to augment blood donation in the COVID‐19 pandemic. The measures should include information about implementation of safety measures to mitigate COVID‐19 transmission at the blood centres and that the act of blood donation does not increase risk of COVID‐19 and therefore the risk of transmission of infection to family.